Impact of a personal history of cutaneous squamous cell carcinoma in the overall survival of cutaneous melanoma patients. Issue 2 (3rd April 2022) - Moro, Ruggero; Campos, Eva; González‐Cuevas, Rubén; Aguerralde‐Martin, Maider; Requena, Celia; Manrique‐Silva, Esperanza; Traves, Victor; Virós, Amaya; Kumar, Rajiv; Nagore, Eduardo
Abstract: Background: There have been previous studies on the association between cutaneous squamous cell carcinoma (cSCC) and cutaneous melanoma (CM) survival, and also the association between skin cancers and relative telomere length (RTL). In this study we analysed the overall survival (OS) of patients with CM and a positive history of cSCC to evaluate the impact of this history on survival and any possible association with RTL. Materials and Methods: A retrospective cohort study on 1613 patients with CM diagnosed between 1 January 2000 and 31 December 2015 at the Instituto Valenciano de Oncología. Contingency tables were used to analyze the association between a positive history of cSCC and other covariates. OS was evaluated using Kaplan–Meier curves and log‐rank test. Cox regression was used to determine the prognostic role of each covariate. Results: Patients with a positive history of cSCC had a shorter OS ( p  < 0.001), but this was not significant at multivariate analysis. The covariates that resulted in independent predictors of shorter OS were gender, localisation, and lymphovascular invasion. Age and Breslow thickness were independent predictors only after 15 months of follow‐up; mitotic rate only between 15 and 65 months; disease stage only below 65 months, and RTL only after 65 months of follow‐up. A positive history of cSCC was not associated with RTL. Conclusions: Our results suggest that CM patients with a positive history of cSCC have a worse OS because it is related to other independent prognostic factors such as male gender and older age.